Resize Public Relations: in search of a theoretical construct which optimizes the communication dynamics between business and social realities - Sánchez de Walther, Amybel (2012)
There is no doubt that in a globalized market (highly competitive and demanding, which seeks excellence, honesty and business creativity) Public Relations must be constructed as a social science, multidisciplinary and flexible, directed not only to the attainment of corporate objectives, but also to follow closely the development of rural communities, the various guilds, unions and NGOs; institutions, State authorities and citizen groups in general.